Classical galactosemia and mutations at the galactose-1-phosphate uridyl transferase (GALT) gene - Tyfield, Linda; Reichardt, Juergen; Fridovich-Keil, Judy; Croke, David T; Elsas II, Louis J; Strobl, Wolfgang; Kozák, Libor; Coskun, Turgay; Novelli, Giuseppe; Okano, Yoshiyuki; Zekanowski, Cezary; Shin, Yoon; et al. (Human mutation, 1999)
Classical galactosemia is caused by a deficiency in activity of the enzyme galactose-1-phosphate uridyl transferase (GALT), which, in turn, is caused by mutations at the GALT gene. The disorder exhibits considerable allelic heterogeneity and, at the end of 1998, more than 150 different base changes were recorded in 24 different populations and ethnic groups in 15 countries worldwide. The mutations most frequently cited are Q188R, K285N, S135L, and N314D. Q188R is the most common mutation in European populations or in those predominantly of European descent. Overall, it accounts for 60-70% of mutant chromosomes, but there are significant differences in its relative frequency in individual populations. Individuals homoallelic for Q188R tend to have a severe phenotype and this is in keeping with the virtually complete loss of enzyme activity observed in in vitro expression systems. Globally, K285N is rarer, but in many European populations it can be found on 25-40% of mutant chromosomes. It is invariably associated with a severe phenotype. S135L is found almost exclusively in African Americans. In vitro expression results are discrepant, but some individuals carrying S135L appear to exhibit GALT activity in some tissues. Duarte 1 (or Los Angeles) and Duarte 2 (or Duarte) variants carry the same amino acid substitution, N314D, even though D1 is associated with increased erythrocyte GALT activity and D2 with reduced activity. N314D is in linkage disequilibrium with other base changes that differ on the D1 and D2 alleles. N314D does not impair GALT activity in in vitro expression systems. However, there are differences in the abundance of GALT protein in lymphoblastoid cells lines from D2 and D1 individuals. It is unclear whether the specific molecular changes that distinguish the D1 and D2 alleles account for the different activities. The considerable genetic heterogeneity documented to date undoubtedly contributes to the phenotypic heterogeneity that is observed in galactosemia. The additional effects of nonallelic variation and other constitutional factors on phenotypic variability remain to be elucidated.
Keywords: introny; Chromosomes, Human, Pair 9; myši; Animals; Galactosemias; Mutation, Missense; exony; myši knockoutované; Polymorphism, Genetic; UTP-Hexose-1-Phosphate Uridylyltransferase; missense mutace; mutace; Mice, Knockout; galaktosemie; Humans; alely; Gene Deletion; polymorfismus genetický; Alleles; lidské chromozomy, pár 9; lidé; Mice; zvířata; delece genu; UDP-galaktosapyrofosforylasa; Mutation; Exons; Introns